Moderating effect of technology readiness towards open and distance learning (ODL) technology acceptance during COVID-19 pandemic / Nur Nadiah Abdul Rahim ... [et al.] - Abdul Rahim, Nur Nadiah; Humaidi, Norshima; Abdul Aziz, Siti Rahayu; Mat Zain, Nurul Hidayah (Universiti Teknologi MARA, 2022)
The COVID-19 pandemic has impacted higher education in Malaysia that requires the academics to transform their teaching style to online teaching. Hence, it is essential for them to be skilful in using new technology in teaching and learning. In Open and Distance Learning (ODL), the academic staff must learn a new environment of learning technology in terms of giving lectures and managing all related ODL documents. In this perspective, technology readiness of the ODL technology plays an important role to enhance the acceptance of using the latest technology in ODL among them. This study was conducted to test the moderating effect of the Technology Readiness of the academic staff towards their acceptance of ODL technology to manage teaching and learning process such as UFUTURE and Google Classrooms. The research model was developed based on Technology Acceptance Model (TAM) and Technology Readiness concept. The online survey was created and then emailed to the academic staff in UiTM Selangor, resulting in 321 responses were received subsequently. The results show that the Technology Readiness factors (Optimism and Innovativeness) strengthen the relationship between Technology Acceptance factors (Perceived Ease of Use and Perceived Usefulness) and intention behaviour to use the ODL technology. Additionally, the direct effect testing has also shown that the related factors influence the intention of the academic staff to use the ODL technology except Insecurity and Discomfort. Technology readiness does play an important role; therefore, it is essential for the university to train academic staff on new ODL technology and it should be planned accordingly.